Effects of the Age–Education Structure of Female Workers on Male Earnings in Brazil. Issue 4 (December 2013) - de Lima Amaral, Ernesto Friedrich; Almeida, Mariana Eugenio; Rios‐Neto, Eduardo Luiz Gonçalves; Potter, Joseph E.
Abstract The main concern of this study is the impact that an increase in female participation within the labor force has on the earnings of males in Brazil. Previous research considered these transitions for male workers, but did not include female workers when estimating various effects on earnings. The 1970, 1980, 1991, and 2000 Brazilian Demographic Censuses were used for this analysis. Results suggest a significant negative impact on male earnings in 1970 as a result of the share of female workers. This effect has been decreasing over time, as the coefficients from more recent years are positive. Changes in age and educational composition make a substantial difference on the estimation of male earnings in Brazil. The method developed in this study is not infallible, but it improves previous estimates by including the relationship among compositional changes, female labor force participation, and earnings, thus going beyond the direct impact of age and education.